Future drought in the dry lands of Asia under the 1.5 and 2.0~°C warming scenarios - Lijuan Miao; Suyuan Li; Feng Zhang; Tiexi Chen; Yunpeng Shan; Yushan Zhang (Earth's Future, 2020)
Drought has become a major threat to local sustainable development in dryland Asia, one of the largest grassland ecosystems in the world. However, empirical- and science-based evidence regarding the extent of drought changes and the future trends of these changes in dryland Asia is variable and incomplete. Here, we first investigate the historical variations in drought conditions in dryland Asia, as measured by the drought intensity and arid area, using three widely used drought indices (the Palmer Drought Severity Index, the Standardized Precipitation Index, and the Standardized Precipitation Evapotranspiration Index). Then, we use Bayesian model averaging to reproduce the future drought conditions under two representative concentration pathways (RCP2.6 and RCP4.5) from the Coupled Model Intercomparison Project Phase 5 Earth system models. The Palmer Drought Severity Index, Standardized Precipitation Index, and Standardized Precipitation Evapotranspiration Index illustrate that dryland Asia has experienced an overall drying trend and an expansion of arid areas over the past 100~years (1901–2016). Both temperature and precipitation are projected to increase under both the 1.5 and 2.0~°C warming scenarios compared with the values from the reference period (1986–2005). The projected drought conditions in the 1.5 and 2.0~°C warming scenarios will worsen, especially across Kazakhstan and Northwest China. We found that the drought conditions under the 2.0~°C warming conditions will not be as severe as those under the 1.5~°C warming conditions due to the mitigating effect of the projected precipitation increase under RCP4.5. These results call for short-term and long-term mitigation and adaptation measurements for drought events in dryland Asia.
Keywords: 330; drought; dryland Asia; 1.5~°C; 2.0~°C; CMIP5